1998
DOI: 10.1007/s007780050063
|View full text |Cite
|
Sign up to set email alerts
|

Integrating reliable memory in databases

Abstract: Recent results in the Rio project at the University of Michigan show that it is possible to create an area of main memory that is as safe as disk from operating system crashes. This paper explores how to integrate the reliable memory provided by the Rio file cache into a database system. Prior studies have analyzed the performance benefits of reliable memory; we focus instead on how different designs affect reliability. We propose three designs for integrating reliable memory into databases: non-persistent dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Very few works have evaluated experimentally the behavior of DBMS in the presence of faults. However, all the experimental evaluation works known in the literature have shown that a non-negligible number of faults are not handled correctly by DBMS [2][3][4][5][6]. While previous papers are "classic" fault injection works that have injected hardware and software faults, our work is, to the best of our knowledge, the first experimental evaluation of a DBMS with operator faults.…”
Section: Introductionmentioning
confidence: 89%
“…Very few works have evaluated experimentally the behavior of DBMS in the presence of faults. However, all the experimental evaluation works known in the literature have shown that a non-negligible number of faults are not handled correctly by DBMS [2][3][4][5][6]. While previous papers are "classic" fault injection works that have injected hardware and software faults, our work is, to the best of our knowledge, the first experimental evaluation of a DBMS with operator faults.…”
Section: Introductionmentioning
confidence: 89%
“…One cluster is denoted as C and the data volume of C is denoted as C d . In the paper we propose a clustering algorithm called equal-capacity clustering algorithm based on k-means [12]. The algorithm divides all units of cache into the number of nodes (n), and each node has the same data volume.…”
Section: Cache Placement Algorithmmentioning
confidence: 99%
“…Prior to NVM, researchers proposed battery-backed DRAM and buffer manager extensions to support recoverability [28]. For instance, [10] uses battery-backed DRAM with an ARIESlike protocol, and assumes page-level I/O for data and log updates.…”
Section: Recoverymentioning
confidence: 99%